Haunting Authorship: The Colonial Entanglement of Space and Body in Cheers, Soldier！ - Xin, Hu (Pacific International Journal, 2025)
Through examining Huang Chunming’s transtextual project Cheers, Soldier!（Zhanshi Ganbei 戰士，乾杯！）, this paper explores how settler authorship becomes structurally unsettled. Across its short story and stage script forms, the narrative centers on the multigenerational conscription of Indigenous men into successive colonial armies. Rather than presenting this history as resolved or representable, the texts reveal a deeper tension: the author’s own position becomes entangled in the return of what cannot be narrated from the outside. While the short story filters Indigenous experience through a reflective first-person voice, the stage script disperses that perspective, incorporating fragmented speech, embodied presence, and performative memory. As narrative control gives way to shared perception, authorship itself shifts from an interpretive authority to a residual structure shaped by absence, vulnerability, and repetition. Through close textual analysis, the paper argues that this transtextual movement is not a linear adaptation, but a redistribution of narrative responsibility. Cheers, Soldier! does not aim to repair historical violence through fiction. Instead, it lingers in the uncertainty of what it means to write from a settler position. The result is not narrative empathy, but narrative haunting: an authorial presence that remains within the frame, no longer centered, but no longer able to withdraw.